Inyiak Upiak Palatiang - Ari Pardi; Martarosa M.Sn; Rafilosa M.Sn (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Inyiak Upiak Palatiang was born in 1900s in Kubu Gadang Hamlet, Nagari Gunuang, Padang Panjang City, he is famous as a pandeka (swordsman) Minangkabau silat girl who controls the flow of silek gunuang (Silat Gunung). (Interview with grandson Inyiak Upiak Palatiang, Fardizal, 20.00WIB, Padang Panjang, January 8, 2017). Inyiak Upiak Palatiang is a Minangkabau martial arts master, when he is 100 years old, he is still active in preserving and preserving the art of Minangkabau culture, even being a teacher of silek tuo (old martial arts), He is also known as a reliable kicker with various dendang creations besides Inyiak Upiak Palatiang also likes to play art Randai tradition. Based on the explanation of the greatness of Inyiak Upiak Palatiang, pengkarya plans to lift it into a musical masterpiece of the archipelago that will be titled "Inyak Upiak Palatiang", with the reason of the name of Inyiak Upiak Palatiang already representing what he cared for during his life. Background of the phenomenon that has been described, it can be formulated a formulation of the creation of the work, that is how to transform the phenomenon of a female character Inyiak Upiak Palatiang , into a musical composition of the archipelago, which will be divided into two sub-works, namely Upiak and Palatiang.